Virtual Attendance: Analysis of an Audiovisual over IP System for Distance Learning in the Spanish Open University (UNED) - Vázquez-Cano, Esteban; Fombona, Javier; Fernández, Alberto (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This article analyzes a system of virtual attendance, called “AVIP” (AudioVisual over Internet Protocol), at the Spanish Open University (UNED) in Spain. UNED, the largest open university in Europe, is the pioneer in distance education in Spain. It currently has more than 300,000 students, 1,300 teachers, and 6,000 tutors all over the world, besides Spain. This university is redefining, on the lines of other universities, many of its academic processes to meet the new requirements of the European Higher Education Area (EHEA). Since its inception, more than 30 years ago, the methodology chosen by UNED has been blended learning. Today, this university combines face-to-face tutorial sessions with new methodological proposals, mediated by ICT. Through a quantitative methodology, the perception of students and tutors of the new model of virtual tutoring, called AVIP Classrooms, was analyzed. The results show that the new model greatly improves the orientation and teaching methodology of tutors. However, it requires training and new approaches to provide a more collaborative and participatory environment for students.